Restructuring law of OHADA commercial companies, comparative research with Frenc Law - (:unkn) unknown (My University, 2015)
In a context of globalization, the african companies have to adapt themselves permanently to economic legal or social contingencies. Conscious of that reality, african legislator set up within the OHADA reform legal measures to allow theme acclimatize to the tendencies and markets pression : the restructuring law which design all the technicals proceedings conceived by the legislator to reorganize the company. Those technicals was inspirated by French law restructuring which has been reorganized. The confrontation of both systems allows to notice that if in the fundamental principles they are the same objectives consisting in substainability of companies for their growth or their survival there are however pratical and technical differences materialized by the recents french reforms.
Keywords: African Research